SARS-CoV-2 Seroprevalence Among Health Care Workers in Major Private and Public Hospitals With COVID-19 Patient's Referral in Tehran, Iran - Darvishian, Maryam; Sharafkhah, Maryam; Mohammadi, Zahra; Sadeghniiat-haghighi, Khosro; Abdollahi, Alireza; Jafary, Mohamadreza; Talaschian, Mona; Tabarsi, Payam; Baghai, Parvaneh; Mardani, Masoud; Shayanrad, Amaneh; Shafighian, Fatemeh; et al. (Frontiers in Public Health, 2022)
Estimating the prevalence of SARS-COV-2 antibody seropositivity among health care workers (HCWs) is crucial. In this study the seroprevalence of anti-SARS-COV-2 antibodies among HCWs of five hospitals of Tehran-Iran with high COVID-9 patient’s referrals during April to June, 2020, was assessed. In this cross-sectional study, HCWs from three public and two private hospitals, selected randomly as a pilot, were included. Participants were asked questions on their demographic characteristics, medical history, hospital role and usage of personal protective equipment (PPE). Iran FDA-approved SARS-CoV-2 ELISA kits were used to detect IgG and IgM antibodies in blood samples. Seroprevalence was estimated on the basis of ELISA test results and adjusted for test performance. Among the 2065 participants, 1825 (88.4%) and 240 (11.6%) HCWs were recruited from the public and private hospitals, respectively. 340 HCWs were tested positive for SARS-COV-2-specific IgG or IgM antibodies and 17.9% of seropositive individuals were asymptomatic. The overall test-performance adjusted seroprevalence estimate among HCWs was 22.6 (95% CI 20.2-25.1) ,and PPE usage was significantly higher among HCWs of public versus private hospitals (66.5% vs. 20.0%). This study found that seroprevalence of SARS-COV-2 among HCWs was higher in private hospitals (37.0%; 95% CI 28.6-46.2) than public hospitals (20.7%; 95% CI 18.2-23.3), and also highest among assistant nurses and nurses, and lowest among janitor/superintendent categories. The PPE usage was especially suboptimal among HCWs in private hospitals. Continued effort in access to adequate PPE, regular screening of hospital staff for detecting asymptomatic personnel, especially during the upcoming wave of infection, are warranted.